Novel gelatin-polyoxometalate based self-assembled pH responsive hydrogels: formulation and in vitro characterization. Issue 8 (16th November 2016) - Azizullah,; Nisar-ur-Rehman,; Liu, Wenjing; Haider, Ali; Kortz, Ulrich; Sohail, Muhammad; Joshi, Sachin A.; Iqbal, Jamshed
Abstract: The purpose of the study was to develop physically cross-linked novel pH-responsive gelatin – Wells–Dawson-type polyoxometalate (POM)-based self-assembled hydrogels using acrylic acid as a pH-responsive monomer. Cross-linking was achieved through electrostatic interactions between the cationic polymer and anionic Wells–Dawson POM [P2 W15 O56 ] 12− . Ammonium persulfate and sodium hydrogen sulfite were used as initiators. The hydrogels were yellowish in color and exhibited low mechanical strength. Swelling, drug release, and pH sensitivity studies were conducted at pH 1.2 and 7.4. pH-dependent swelling and release of [P2 W15 O56 ] 12− from the prepared hydrogels were observed, with a maximum at pH 7.4. The hydrogels were characterized by thermogravimetric analysis, differential scanning calorimetry, scanning electron microscopy, and Fourier transform infrared spectroscopy for evaluation of the surface morphology, hydrogel confirmation, and thermal properties. The results obtained confirmed the development of a gelatin–POM-based self-assembled hydrogel. It can be concluded that as a result of successful physical cross linking, the prepared hydrogels possess desired characteristics of a drug delivery system and can hence be used for a controlled delivery of the encapsulated polyanions. .